Marianne Moore - Bloom, Harold. (Chelsea House, 1987)
A collection of critical essays on the poetry of Marianne Moore. Also includes a chronology of events in her life.
Includes index.
Bibliography: p. 173-175
A collection of critical essays on the poetry of Marianne Moore. Also includes a chronology of events in her life.